PELAKSANAAN DIGITALISASI PELAYANAN PADA WEBSITE “SIPENDUK ONLINE” DI DISDUKCAPIL KABUPATEN SEMARANG - Ramadhani, Shinta Putri; -, Yuwanto -; Marlina, Neny - (Journal of Politic and Government Studies, 2024)
This research discusses the digitalization of services on the "Sipenduk Online" website in Population and Civil Registration Office of Semarang Regency. The application of digitalization of services in public service institutions has become commonplace. One form of digitalization of services created by Population and Civil Registration Office of Semarang Regency is Sipenduk Online. The policy in the form of Centralized SIAK makes online services on "Sipenduk Online" limited. The impermissibility of applications attached to the SIAK system makes Population and Civil Registration Office switch the online service platform to the form of a website. This research uses E-Government Theory from Indrajit (2016) and uses research methods in the form of descriptive qualitative approaches. Data collection techniques in this study were carried out by interviews, observation, and documentation. The results showed that the digitalization of services at "Sipenduk Online" in Population and Civil Registration Office of Semarang Regency has not achieved success. This is because there are still various fundamental problems related to the management of "Sipenduk Online". This is shown by the foundation of formation that is not strong, facilities provided to handle various jobs, unsystematic management structures, unfulfilled human resources, the absence of specific budget allocations regarding Sipenduk Online, and the mismatch of benefits that should be received by the community as users.